The determination of the pain relief approaches in emergency trauma units [Acil travma ünitelerinde aǧri geçirme yaklaşimlarinin belirlenmesi] - (:unkn) unknown (My University, 2006)
This definitive study has been performed to assess the approach to pain relief in emergency trauma units. The study population consisted of patients seen at the emergency trauma clinics of three different, state-owned, research hospitals in the city of Istanbul. A total of 375 patients with an age range of 18-65 were included. The data were obtained from an 18 question data sheet. Trauma was caused by a fall in 46.1% of the patients and 66.7% of the cases were out of building. Blunt trauma was the cause in 85.6%, 31.2% had head trauma, 38.1% exteremity injuries. Of the patients enrolled in the study, only 17.1% (64 patients) had recieved analgesics. The most common analgesic medication group used was Nonsteroid Anti Inflammatory Drugs (NSAID). According to these results, 82.9% of patients with pain due to trauma had not recieved analgesics and it can be concluded that pain in trauma patients is undertreated.
Keywords: Analgesia; Emergency room; Pain; Trauma